2021
DOI: 10.1111/imj.14749
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and efficacy of sacubitril/valsartan in clinical practice

Abstract: Background Heart failure (HF) is a major cause of morbidity and mortality. Sacubitril/valsartan has demonstrated reductions in HF hospitalisation, and all‐cause mortality in patients with heart failure with reduced ejection fraction. Aims To assess the tolerability and efficacy of sacubitril/valsartan in an intention to treat patient cohort. Methods Sixty‐five patients who were commenced on sacubitril/valsartan in 2017 at a major metropolitan centre in Victoria were retrospectively audited. Clinical outcomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Baseline SBP is, of course, the primary determinant for achieving of higher Sac/Val dose. In our cohort, a significant reduction in BP was observed during follow‐up, and hypotension still represents, in several observational studies, the main determinant of ineffective up‐titration 24 . Elderly patients are frailer, with a higher co‐morbidity burden and, therefore, more prone to adverse effects during up‐titration, compared with the selected trial population 7 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Baseline SBP is, of course, the primary determinant for achieving of higher Sac/Val dose. In our cohort, a significant reduction in BP was observed during follow‐up, and hypotension still represents, in several observational studies, the main determinant of ineffective up‐titration 24 . Elderly patients are frailer, with a higher co‐morbidity burden and, therefore, more prone to adverse effects during up‐titration, compared with the selected trial population 7 .…”
Section: Discussionmentioning
confidence: 71%
“…In our cohort, a significant reduction in BP was observed during follow‐up, and hypotension still represents, in several observational studies, the main determinant of ineffective up‐titration. 24 Elderly patients are frailer, with a higher co‐morbidity burden and, therefore, more prone to adverse effects during up‐titration, compared with the selected trial population. 7 Finally, as expected, the baseline tolerability of ACEi/ARBs maximum dose plays a key role in achieving of Sac/Val target dose, in line with previous literature findings.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend up-titration of ARNI to the highest dose tolerated by the patient, with a minimal effective daily dose of 48/52 mg 1,14,33 . Due to the blood-pressure-lowering effect of ARNI, maximal doses are frequently not well tolerated by patients 33–35 . In a recent study evaluating the tolerability of an ARNI up-titration, only 14% of patients tolerated the maximal daily dose of 194/206 mg, whereas nearly a quarter of the patients in this study remained on the minimal daily dose of 48/52 mg 33 .…”
Section: Discussionmentioning
confidence: 68%
“…As reported by Kraai et al , 32 more than half of patients with symptomatic heart failure prefer to improve their quality of life, even at the expense of longevity. Current guidelines recommend up-titration of ARNI to the highest dose tolerated by the patient, with a minimal effective daily dose of 48/52 mg 1,14,33 . Due to the blood-pressure-lowering effect of ARNI, maximal doses are frequently not well tolerated by patients 33–35 .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study reported significant improvements in NYHA class ( P < 0.05) and the quality of life scores on the EQ5D-VAS (standardized instrument to measure health outcomes) ( P < 0.05) in HFrEF patients treated with sacubitril/valsartan after 6 to 12 months of follow-up. 50 In another retrospective cohort study, sacubitril/valsartan therapy obviously improved NYHA class from 2.3 ± 0.6 to 1.8 ± 0.5 ( P < 0.001), increased LVEF from 31.2 ± 7.0% to 37.3 ± 10.5% ( P < 0.001) and decreased the level of NT-pro-BNP from 3884 ± 4871 pg/ml to 1975.3 ± 3006.6 pg/ml ( P = 0.0001) in HFrEF patients after 316.1 ± 155.9-day follow-up. 51 However, given the weak level of evidence from observational studies, RCTs and meta-analyses should be implemented.…”
Section: Efficacy Of Sacubitril/valsartan In the Treatment Of Hfmentioning
confidence: 99%